2015
DOI: 10.1007/s11745-015-4038-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Rapid Identification, and Quantification of Adulterants in Extra Virgin Olive Oil Using Near‐Infrared Spectroscopy and Chemometrics

Abstract: A new, rapid Fourier transform near infrared (FT-NIR) spectroscopic procedure is described to screen for the authenticity of extra virgin olive oils (EVOO) and to determine the kind and amount of an adulterant in EVOO. To screen EVOO, a partial least squares (PLS1) calibration model was developed to estimate a newly created FT-NIR index based mainly on the relative intensities of two unique carbonyl overtone absorptions in the FT-NIR spectra of EVOO and other mixtures attributed to volatile (5280 cm(-1)) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(122 citation statements)
references
References 28 publications
5
116
1
Order By: Relevance
“…The comparison of FT‐NIR spectra for authentic EVOO and adulterant oils in the 5150 to 5350 cm −1 range revealed the presence of significant spectral differences (Figure ), as was first reported by Azizian and others (). In particular, significant intensity variation was observed for the weak feature near 5280 cm −1 attributed to the second overtone of the C═O stretching vibration.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The comparison of FT‐NIR spectra for authentic EVOO and adulterant oils in the 5150 to 5350 cm −1 range revealed the presence of significant spectral differences (Figure ), as was first reported by Azizian and others (). In particular, significant intensity variation was observed for the weak feature near 5280 cm −1 attributed to the second overtone of the C═O stretching vibration.…”
Section: Resultssupporting
confidence: 77%
“…No 25 Global Method for the detection of extraneous oils in olive oils (IOC ). In addition, all the reference EVOO products used in the present study were found to be authentic based on our published FT‐NIR and PLS procedure (Azizian and others ). The CI analysis and the SIMCA classification model were validated using 3 sample sets consisted of the following: (1) 10 Adulterant oils consisting of 9 vegetable oils obtained from local grocery stores, and a palm olein sample that was purchased from a local store in Indonesia, (2) 20 Test mixtures prepared with one of the authentic EVOO, namely California sample S9, that was spiked with 10% and 20% (w/w) of each of the 10 adulterants, and (3) an additional set of 7 randomly selected authentic EVOO samples acquired from California.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, due to it was local specialty, few reports about the detection of camellia oil adulteration by NIR were found. Some adulteration detection for olive oil could be treated as references, [19][20][21] as the similarities of camellia oil with olive oil in physical and chemical constants.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy and near-infrared spectroscopy (NIR) are two promising analytical techniques being investigated as screening tools to identify EMA in food products (Baeten et al 2005; Kasemsumran et al 2007; Cheng et al 2010; Moore et al 2012b; Azizian et al 2015). Common benefits of these two methods, compared with other technologies such as LC-MS/MS (MacMahon et al 2012), ELISA (Moatsou & Anifantakis 2003) and GC-MS/MS (Hong et al 2009), include simplicity, limited need for sample pre-treatment, rapid measurements, rugged instrumentation, portable systems availability and high-throughput analysis.…”
Section: Introductionmentioning
confidence: 99%